Impor Mobil Suzuki dalam Perkembangan Industri Otomotif di Indonesia - Mohamad Rafi; Rama Iqbal Yudhistira Sujana; Heykel Revelyn Fahrezy; Mohamad Zein Saleh (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The Suzuki XL7 is one of the car models produced by PT Suzuki Indomobil Sales (SIS) in Indonesia. Since its launch in 2020, the car has undergone significant development, especially with the introduction of a hybrid variant in 2023. This article aims to analyze the import and export phenomenon of the Suzuki XL7 from 2019 to 2024, as well as the challenges faced in the process. Through an in-depth literature review, this research will explore the various variables that influence the success of the Suzuki XL7 in the domestic and international markets. The research method used is literature analysis, which involves collecting data from various reliable sources. The discussion will cover market analysis, marketing strategies, as well as case studies related to challenges and solutions in the face of global competition. The conclusion of this research will provide a comprehensive overview of the Suzuki XL7's position in the Indonesian and global automotive industry.